Out of Necessity Сomes Virtue: A Preliminary Index of “Hagiographical Icons” in the Byzantine and Medieval Wall-Painting in Southern Italy - Riccardi, Lorenzo (Actual Problems of Theory and History of Art, 2013)
In Southern Italy there are several “mural icons”, that seem to be close relatives of the so-called “Vita icons”, wherein the image of a saint (standing or half-length portrait) is surrounded by several scenes on all four sides, in which there are the stories of his/her life. I would like to propose a first and preliminary index of these wall paintings, wide-spread in Puglia, Calabria, Basilicata e Campania during the 12th‒15th cc.